Association between lowering heart rate during IMPELLA support and favorable short-term outcome in patients with cardiogenic shock. (14th October 2021) - Maemura, K; Ikeda, Y; Eda, Y; Oki, T; Yazaki, M; Fujita, T; Iida, Y; Nabeta, T; Ishii, S; Koriyama, K; Maekawa, E; Koitabashi, T; et al.
Abstract: Background: Impella has been increasingly used in patients with cardiogenic shock (CGS). Target values for clinical indices for appropriate management of Impella have not yet been established. Purpose: We aimed to elucidate the association between heat rate (HR) during Impella treatment in patients with CGS and clinical outcomes. Methods and results: We retrospectively evaluated 62 patients (68±14 years; male 77%) with CGS receiving temporary circulatory support with the Impella between February 1, 2019, and February 31, 2021. The primary end point was 30-day mortality. Clinical characteristics, laboratory and hemodynamic markers at implantation of Impella (baseline), 12, 24 hr after implantation, and removal of Impella were assessed. There were 28 patients with concomitant use of extracorporeal membrane oxygenation (ECMO). Treatment periods using Impella were 8±6 days. After excluding 11 patients who died during Impella support, the relationship between clinical indicators at each time points and 30-day mortality was evaluated. There were 22 patients (43%) with 30-day mortality. Factors associated with 30-day mortality were: female, ECMO, higher 24-hr lactate level, lower 24-hr cardiac power output, and higher HR at removal. Lower HR of ≤81 bpm at removal was found to most accurately predict lower 30-day mortality (Figure 1). Higher increases in dose of beta-blockers during Impella support and lower absolute doses of norepinephrine at removal were correlated with decreases in HR during Impella support. Conclusions: In patients with CGS treated with Impella, lower HR at removal was associated with lower incidence of 30-day mortality. Lowering HR during Impella treatment was recognized as a simple indicator for favorable clinical outcomes in patients with CGS. It was suggested that chronotropic interventions during Impella treatment may be novel therapeutic options in patients with CGS. FUNDunding Acknowledgement: Type of funding sources: None.